Pengaruh Produktivitas Kerja terhadap Kompensasi pada PT Sasjam Riri di Kabupaten Gianyar - Ramadhani, Dwi; Trianasari, Trianasari (Jurnal Ilmiah Akuntansi dan Humanika, 2021)
This study aims to obtain explanative findings about the impact of work productivity on compensation at PT Sasjam Riri. The design of this research was causal quantitative. The subjects of this study were all 59 employees of PT Sasjam Riri. The object of this research focused on work productivity and compensation variables.Â The data collection technique was a survey using questionnaire as the research instrument. The data were then analyzed using simple linear regression. The results obtained in the study indicate that work productivity has a positive and significant effect on compensation.